Порівняння імпедансних ланок для перетворювачів з джерелом напруги - Гусев, О.О.; Чуб, А.І.; Вінніков, Д.В. (Технічна електродинаміка, 2015)
Розглянуто основні існуючі на даний момент базові імпедансні ланки для перетворювачів з джерелом напруги. Наведено детальний аналіз їхніх переваг та недоліків, сфери застосування. Окремо розглянуто можливі варіанти модифікації імпедансних ланок з наведеними прикладами. Показано принцип побудови ізольованих перетворювачів на основі імпедансних ланок. Рассмотрены основные существующие на данный момент базовые импедансные звенья для преобразователей
с источником напряжения. Приведен подробный анализ их преимуществ и недостатков, области применения.
Отдельно рассмотрены возможные варианты модификации импедансных звеньев с приведенными примерами.
Показано принцип построения изолированных преобразователей на основе импедансных звеньев. Impedance networks cover the entire realm of electric power conversion in a wide range of applications. Many converter
topologies are presented in the literature in order to overcome the limitations of the traditional voltage source,
current source, classical buck-boost, unidirectional and bidirectional converter topologies. This paper presents review
of the main exist impedance-source networks for voltage-fed converter applications. The detailed analysis of their pros
and cons is revealed. Boost factor of the different impedance networks is compared. The impedance networks that are
based on the coupled inductors can have higher boost performance due to the adjustable turn’s ratio of the windings.
The comparison in terms of input current behavior is presented as well. Modification examples of the impedancesourced
converters are separately considered. Design principles of the isolated and cascaded converters based on the
impedance-source networks are shown. The field of application is discussed. Doe to the wide voltage regulation range
along with cross conduction immunity discussed solutions are promising for the renewable energy applications.